An iterated local search approach for carbon footprint optimisation in an intercloud environment. (2015) - Justafort, Valerie D.; Beaubrun, Ronald; Pierre, Samuel
In this paper, we address the problem of virtual machine (VM) placement in an InterCloud with regard to the reduction of the environmental impact of such environment. We propose a mathematical formulation based on a smart workload consolidation method and a cooling maximisation technique that considers the dynamic behaviour of the cooling fans. As the virtual machine placement problem (VMPP) is classified as an NP-hard problem, we propose an implementation of the iterated local search (ILS) algorithm, ILS_CBF, in order to find good solutions in a reasonable time. Computational results allow to identify the parameters that reduce the carbon footprint costs. The comparison of the proposed heuristic with the exact method and other algorithms demonstrate that the obtained costs are relatively close to the lower bounds, ranging from 0% to a maximum distance less than 2.6%, and allow a good tradeoff between the quality of the solution and the computational time.